Anoctamin-1 in the Juvenile Rat Urinary Bladder - Bijos, Dominika A.; Drake, Marcus J.; Vahabi, Bahareh (PLOS ONE, 2014)
Purpose To investigate presence, location and functional role of calcium-activated chloride channel (CaCC) Anoctamin-1 (Ano1) in rat urinary bladder. Materials and Methods Bladders from 3 week old Wistar rats were studied. End-point PCR on total mRNA was used to assess the expression of Ano1. Immunofluorescent labelling of whole mount bladder tissue imaged with confocal microscope allowed localization of Ano1 and vimentin immunopositive cells. The effects of CaCC blockers: niflumic acid (NFA) (3,10,30 µM) and 5-Nitro-2-(3-phenylpropylamino)benzoic acid (NPPB) (10, 30 µM) on spontaneous phasic contractile activity of intact (with mucosa) and denuded (without mucosa) detrusor strips were measured under isometric tension in organ baths (n = 141, N = 60). Results Ano1 expression was found at mRNA level in mucosa and detrusor layers. Confocal microscopy revealed presence of Ano1 immunopositive cells in mucosa and in detrusor layers; a subpopulation of vimentin positive cells expressed Ano1. Both chloride channel blockers reduced the amplitude and frequency of phasic contractions in denuded and intact strips. Conclusions Ano1 is expressed in rat urinary bladder and is present in cells sharing markers with interstitial cells. CaCC blockers reduced phasic activity of the bladder tissue. Ano1 is expressed in the bladder and plays a role in its spontaneous phasic contractile activity.